Prediction of the anti‐RhD donor population size for managerial decision‐making. Issue 2 (14th April 2016) - van Hoeven, L. R.; Berkowska, M. A.; Verhagen, O. J. H. M.; Koffijberg, H.; van der Schoot, C. E.; Janssen, M. P.
Abstract : Background: Rhesus D (RhD)‐negative women pregnant with a RhD‐positive child receive prophylactic injections to prevent haemolytic disease of the newborn. Because of the success of the prophylaxis, the number of naturally immunized women has decreased, thereby also decreasing the number of potential donors who provide the plasma from which the prophylaxis is made. As the current donor pool is ageing, the availability of the prophylaxis is threatened. Objectives: Objectives are to investigate whether the anti‐D population and the changes therein can be described by a relatively simple model, to determine the impact of ageing of the anti‐D donors on the decline of the population and how many new donors should be recruited to meet future supply demand. Methods: Data on Dutch anti‐D donors in 1994–2013 were used to simulate the donor population size and age composition for various donor recruitment scenarios. Results: With a continuous influx of 27 new donors per year and a donor stopping rate of 10% per year, the population size will stabilize at 195 donors, with 2·3% of donors stopping annually due to reaching the donor age limit. A formula is derived to estimate which donor recruitment and retention efforts are required to maintain a prespecified donor pool. Conclusion: A relatively simple model can already describe and predict the size of the anti‐D donor population and the impact of ageing accurately.